Interactions between leukemia and feeders in co-cultivation under hypoxia - Sikorová, Miriama; Klener, Pavel; Tonarová, Pavla; Kalbáčová, Marie Hubálek (BMC cancer, 2025)
BACKGROUND: Leukemia is driven by complex interactions within the inherently hypoxic bone marrow microenvironment, impacting both disease progression and therapeutic resistance. Co-cultivation of leukemic cells with feeder cells has emerged as a valuable tool to mimic the bone marrow niche. This study explores the interplay between human commercial SD-1 and patient-derived UPF26K leukemic cell lines with feeders - human fibroblasts (NHDF) and mesenchymal stem cells (hMSCs) under normoxic and hypoxic conditions. RESULTS: Co-cultivation with feeders significantly enhances proliferation and glycolytic activity in the SD-1 cells, improving their viability, while this interaction inhibits the growth and glucose metabolism of the feeders, particularly NHDF. In contrast, UPF26K cells show reduced proliferation when co-cultivated with the feeders while this interaction stimulates NHDF and hMSCs proliferation and glycolysis but reduce their mitochondrial metabolism with hypoxia amplifying these effects. CONCLUSIONS: Cells that switch to glycolysis during co-cultivation, particularly under hypoxia, benefit most from these low oxygen conditions. Due to this leukemic cells' response heterogeneity, targeting microenvironmental interactions and oxygen levels is crucial for personalized leukemia therapy. Advancing co-cultivation models, particularly through innovations like spheroids, can further enhance in vitro studies of primary leukemic cells and support the testing of novel therapies.
Keywords: kokultivační techniky; Co-cultivation; proliferace buněk; Hypoxia; mezenchymální kmenové buňky; Cell Line, Tumor; Cell Hypoxia; Mitochondria; Fibroblasts; nádorové mikroprostředí; Tumor microenvironment; lidé; Feeders; fibroblasty; mitochondrie; Mesenchymal Stem Cells; Coculture Techniques; leukemie; Cell Proliferation; Leukemia; Tumor Microenvironment; glykolýza; Glycolysis; Leukemic cells; hypoxie buňky; nádorové buněčné linie; Humans